2021
DOI: 10.4081/monaldi.2021.1724
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and risk factors for mortality among COVID-19 inpatients at a tertiary care centre in Bengaluru, India

Abstract: COVID-19 is an emerging viral disease affecting more than 200 countries worldwide and it present with varied clinical profile throughout the world. Without effective drugs to cure COVID-19, early identification and control of risk factors are important measures to combat COVID-19.  This study was conducted to determine the clinical profile and risk factors associated with mortality among COVID-19 patients in a tertiary care hospital in South India. This record-based longitudinal study was conducted by reviewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Finally, we included 34 studies which included 23,034 patients totally, of which 14,786 patients were male and 8,208 were females. [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 ] One study did not mention distribution of the sample size between male and female. All the 34 studies were based on Indian population and were performed at different hospitals in India.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we included 34 studies which included 23,034 patients totally, of which 14,786 patients were male and 8,208 were females. [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 ] One study did not mention distribution of the sample size between male and female. All the 34 studies were based on Indian population and were performed at different hospitals in India.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the majority of the deaths (53%) occurred in the older age group of more than 60 years, which was similar to findings by Priya S et al . [ 7 ] in which 59% of deaths occurred in the older age group and various studies[ 5 24 25 26 27 28 ] across the globe. Age-related factors such as declining immune functions, variations in quality and quantity of mucins and glycoproteins on the mucosal barriers and a gradual decline in clearing the inhaled particles could be attributed to increased risk of mortality among the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Marimuthu Y et al . [ 5 ] reported that 1.4 (95% CI, 0.6–3.0) times in 41–50 years of age group, male gender [OR 1.7 (95% CI, 1.1–2.6)], smoking [OR 6.2 (95% CI, 3.6–10.8)] and co-morbidities [OR 4.0 (95% CI, 2.5–6.3)] were significantly associated with increased mortality among COVID-19 patients. The study conducted in a rural part of India by Priya S[ 7 ] reported the same, indicating that the presence of these multiple risk factors will increase the mortality among the COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 114 eligible studies 2 , 3 , 4 , 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Tableunclassified